A randomized, double-blind placebo-controlled study of intranasal standardized cinnamon bark extract for seasonal allergic rhinitis. (December 2019) - Steels, Eleanor; Steels, Elizabeth; Deshpande, Pallavi; Thakurdesai, Prasad; Dighe, Satish; Collet, Trudi
Abstract: Objectives: The aim of the study was to assess the safety and efficacy of a nasal spray containing a polyphenol-rich standardized extract of cinnamon bark ( Cinnamomum zeylanicum ) (IND02) for the treatment of seasonal allergic rhinitis (SAR). Methods: This study was a randomized, double-blind, placebo-controlled study conducted in otherwise healthy men and women, aged between 18 and 75 years old, who were experiencing acute SAR symptoms. Participants were randomized in a 1:1 ratio to a nasal spray containing either IND02 (100 μg/100 μL) or matching placebo in each nostril, twice a day, for seven days. Results: The outcome measures were the rhinoconjunctivitis quality of life questionnaire (RQLQ), the total daily symptom score comprising of day-time nasal, day-time eye, and night-time nasal symptom scores, the Work Productivity and Activities Impairment (WPAI:SHP), the Pittsburgh Sleep Quality Index (PSQI), the Perceived Stress Scale (PSS) and laboratory clinical parameters. Results: The IND02 group showed a statistically and clinically significant reduction in total RQLQ and the sub-domains; activity limitation, sleep problems, nose symptoms, eye symptoms, non-nose/eye symptoms, practical problems and emotional function. There was a significant reduction in the total daily symptom score and sub-domains of total day-time nasal, total day-time eye and total night-time nasal symptoms scores, and total work impairment and regular activity impairment in the IND02 group compared with the placebo group after treatment. The laboratory clinical parameters remained within healthy normal reference range. Conclusion: The use of a nasal spray of a standardized extract of cinnamon bark (IND02) over seven days reduced symptom severity and improved quality of life, work productivity and regular daily activities in participants experiencing SAR.